On Theology in the Academy - Blum, Jason N. (Bulletin for the study of religion, 2019)
Recently, theology has garnered renewed attention in the academy. For various reasons, both theologians and some religious studies scholars have argued that theology deserves to be brought into greater dialogue with other disciplines, and some have even argued that theology ought to be taught in the public university. There are interesting arguments to be made that theology is more similar to other disciplines than might initially be supposed, and even that it is at the cutting edge of certain recent developments in scholarship more broadly. There are also, however, noteworthy barriers to incorporating theology more fully into the academy, and these may present significant challenges to inter-disciplinary dialogue and the possibility of productive exchange between theology and other areas of research.